Kebertahanan bahasa daerah dalam konteks kebijakan bahasa nasional Indonesia: Kasus bahasa Batak - Rosmawaty, Rosmawaty (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2013)
The purpose of this study was to describe the influence of Batak cultural values and religious practices on Batak language maintenance. The results of this qualitative study indicate that the influence of Batak cultural values and religious practices varies among Angkola/Mandailing, Toba, Simalungun, Karo, and Pakpak/Dairi communities. Variations in language maintenance create a continuum in the implementation of Indonesian as the national language, particularly in North Sumatra.